Comparison of Oral Ivermectin and Permethrin 5% Lotion in Treatment of Pediculosis Capitis - Farid, Huma; Muzaffar, Bushra; Siddiqui, Muhammad Adeel; Hussain, Majid; Sajjad, Danyal; Nigar, Zahra (Pakistan Armed Forces Medical Journal, 2024)
Objective: To study the efficacy of oral Ivermectin compared with Permethrin 5% lotion for pediculosis capitis management.Study Design: Randomized controlled trial.Place and Duration of Study: Department of Dermatology, Combined Military Hospital, Abbottabad Pakistan, from Mar to Aug 2022.Methodology: We enrolled 60 patients, aged between 8 to 36 years. Group A, with 30 patients, was given topical 5% Permethrin lotion in two applications, seven days apart. Group B, also with 30 patients and having more than 15 kg weight, was given oral Ivermectin 200 microgram per kilogram on Day 1 and repeated after 7 days with patients reassessed at Day 7 and 15. Demographic information along with frequency and percentages were calculated for qualitative variables by using SPSS version 26.0. To determine statistical significance, p-value of ≤0.05 was set as significant, and χ2-square test was used.Results: On comparison of efficacy in group A (Permethrin-5%) only 14(46.6%) of the patients showed complete recovery, however, the majority 16(53.4%) of patients needed second dose and a few still had symptoms, while in group B (oral Ivermectin) majority 25(83.3%) of patients recovered at first dose whereas only 5(16.7%) patients needed second dose for complete recovery and no single patient had any symptoms after administration of second dose (p-value≤0.05).Conclusions: The effectiveness of oral Ivermectin was much greater than that of 5% Permethrin lotion.